Inherited Deletion of 1q, Hyperparathyroidism and Signs of Y-chromosomal Influence in a Patient with Turner Syndrome - Alejandro F. Siller; Alex Shimony; Marwan Shinawi; Ina Amarillo; Louis P. Dehner; Katherine Semenkovich; Ana María Arbeláez (Galenos Yayincilik, 2019)
We report a detailed phenotypic, cytogenetic and molecular characterization of a patient prenatally diagnosed with Turner syndrome (TS). In addition to having typical TS clinical characteristics including webbed neck, high arched palate and coarctation of the aorta, the patient had features less frequently seen in TS. These included recurrent parathyroid adenomas, growth along the 75th-90th centiles on the TS height curve despite minimal treatment with growth hormone, behavioral problems and evidence of gonadal dysgenesis with testicular-like structures, such as seminiferous tubules lined by Sertoli cells and a contiguous nodule of Leydig cells. While fluorescence in situ hybridization (FISH) failed to detect Y-chromosome material in gonadal tissue or blood samples, chromosomal microarray analysis (CMA) confirmed X monosomy and a 4.69 Mb copy number loss on 1q31.2q31.3 (bp 192,715,814 to 197,401,180). This region contains the CDC73 gene which has been associated with hyperparathyroidism-jaw tumor syndrome, features of which include recurrent, functional parathyroid adenomas and behavioral issues. This case illustrates how atypical features in a TS patient, such as robust growth and recurrent parathyroid adenomas, may suggest an underlying molecular etiology that should be explored by additional genetic diagnostic modalities. It is therefore appropriate in such cases to conduct further genetic testing, such as CMA and FISH, to explore other diagnostic possibilities and possibly prevent further complications.